Gender Disparities in Symptoms of Depression After Medical School Exams and Student Coping Strategies for Postexam Depression Symptoms. (January 2022) - Arabatzis, Taxiarhia J; Marsidi, Jennifer; Ashraf, Muhammad; Supino, Christina; Smith, Ryan
CONTEXT: Little research exists to determine if medical students experience symptoms of depression after examinations and if symptoms vary by gender. OBJECTIVES: Determine if is there a difference between male and female medical students in the number of symptoms of major depressive disorder (MDD) experienced after exams, as well as which coping strategies are used by students to alleviate depression symptoms. METHODS: An anonymous and secure survey was sent via university email to first, second, and third-year medical students after exams for 2 consecutive exam periods. Surveys that were not fully completed were excluded from the analysis. RESULTS: A total of 162 out of 550 students completed the survey for a response rate of 30%. Overall, a greater proportion of female students experienced more symptoms of depression compared to males. This was statistically significant for the Diagnostic and Statistical Manual of Mental Disorders 5th Edition symptoms of MDD: depressed mood, anhedonia, changes in sleep, fatigue, and difficulty with concentration after exams compared to their male counterparts. Male first-year medical students experienced higher rates of depression compared to their third-year counterparts. Most students exhibited coping strategies that helped them feel less depressed. The 3 most common coping strategies reported were: reaching out to social support networks, physical activity/exercise, and engaging in hobbies. CONCLUSIONS: Both gender and year in a medical school play a role in the number of symptoms of depression experienced after medical school exams. Recognizing that examinations can be a trigger of depressive symptoms in medical students, particularly female and first-year students, has important implications on student mental health. Helping students recognize these symptoms and employ healthy coping strategies may further help alleviate these symptoms. Long-term consequences of experiencing symptoms of depression after recurrent exams in medical school are unknown and require further research.